Mapping Research on Educational Supervision in Science Practicums to Improve Students’ Science Process Skills - Rizka Sofia Irawan (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2025)
Educational supervision plays a crucial role in improving the quality of instruction, particularly in science practicum activities aimed at developing students’ science process skills. This study aims to describe research trends on the implementation of educational supervision in science practicums to enhance science process skills. The method employed is descriptive-analytical by reviewing 1,000 documents indexed in Google Scholar from 2016 to 2025 using Publish or Perish and Dimensions AI. The results show a dynamic pattern of publication growth, with a significant increase from 2016 to 2020 followed by fluctuations in subsequent years. Most publications are journal articles, indicating strong peer-reviewed scholarly attention in this field. Bibliometric mapping identifies four dominant themes: learning quality, laboratory management, teacher professional development, and the strengthening of science process skills. These findings confirm that well-planned and collaborative educational supervision in science practicum activities contributes to improving both teacher competence and students’ scientific abilities. The implications suggest that the results of this study can serve as a reference for teachers, schools, and supervisors in designing supervision strategies that are more effective, relevant, and sustainable.